Heparinised Clotting Factor Concentrates in Patients with Christmas Disease and Liver Disease - Preston, F. E; Malia, R. G; Lilleyman, J. S; Blackburn, E. K (Thrombosis and Haemostasis, 1977)
Evidence has been sought of activation of the coagulation system in two groups of patients following the infusion of two heparinised clotting factor concentrates. No changes were detected in 13 patients with mild hepatic dysfunction. In six studies on patients with Christmas disease induced abnormalities occurred in only one. Activation of the coagulation mechanism did not occur in another individual who had received the same batch of material.